Neuromuscular, biomechanical, and energetic adjustments following repeated bouts of downhill running - Arash Khassetarash; Gianluca Vernillo; Renata L. Krüger; W. Brent Edwards; Guillaume Y. Millet (Elsevier, 2022)
Purpose: This study used downhill running as a model to investigate the repeated bout effect (RBE) on neuromuscular performance, running biomechanics, and metabolic cost of running. Methods: Ten healthy recreational male runners performed two 30-min bouts of downhill running (DR1 and DR2) at a -20% slope and 2.8 m/s 3 weeks apart. Neuromuscular fatigue, level running biomechanics during slow and fast running, and running economy parameters were recorded immediately before and after the downhill bouts, and at 24 h, 48 h, 72 h, 96 h, and 168 h thereafter (i.e., follow-up days). Results: An RBE was confirmed by attenuated muscle soreness and serum creatine kinase rise after DR2 compared to DR1. An RBE was also observed in maximum voluntary contraction (MVC) force loss and voluntary activation where DR2 resulted in attenuated MVC force loss and voluntary activation immediately after the run and during follow-up days. The downhill running protocol significantly influenced level running biomechanics; an RBE was observed in which center of mass excursion and, therefore, lower-extremity compliance were greater during follow-up days after DR1 compared to DR2. The observed changes in level running biomechanics did not influence the energy cost of running. Conclusion: This study demonstrated evidence of adaptation in neural drive as well as biomechanical changes with the RBE after DR. The higher neural drive resulted in attenuated MVC force loss after the second bout. It can be concluded that the RBE after downhill running manifests as changes to global and central fatigue parameters and running biomechanics without substantially altering the energy cost of running.